The tax system of Liberia : report.of the Tax Mission - Tax Mission; Shoup, Carl S. (New York : Distributed by Columbia University Press, 1970)
A detailed and comprehensive description of the existing tax system in Liberia
Includes bibliographical references.
obn 22/01/2019
Loans
Keywords: Taxation; Liberia